Absence of 1061C deletion in A2 blood subgroup validated through gene sequencing in the Malaysian population - Anbukarsu, Aruna; Samat, Mohd Nazif; Salleh, Mohd Nazil (Life Sciences, Medicine and Biomedicine, 2019)
ABO blood grouping is an important antigenic blood typing tools in blood transfusion and organ transplants. Mismatching of blood during transfusion would lead to undesired transfusion reactions. Due to rare occurrence of rare blood group such as A2 subtype, regular blood grouping technique would have missed the identification of blood group. In this study, the identification of A2 subgroup using routine serological technique was validated via DNA sequencing technique. A total of 656 students participated in this study consist of Malay (87.0 %), Chinese (0.4 %), Indian (11.4 %) and others ethnic group (0.9%) respectively. Monoclonal antisera A, B, AB, D, A1 lectin and H lectin were used to identify the antigen on red blood cells. DNA sequence analysis was applied to examine single nucleotide polymorphisms (SNPs) at position 467 (substitution of C>T) and 1061 (deletion of C) on coding region of ABO gene. Our findings showed of 656 blood samples, 256 (39.0%) were blood group O, 190 (29.0%) were blood group B, 179 (27.3%) were blood group A and 31(4.7%) were blood group AB. The frequency of A1 subgroup is 177 (99.0%) and A2 subgroup is 2 (1.0%). From 179 A blood group, only 2 samples showed negative reaction towards anti-A1 lectin. DNA sequence analysis revealed the SNPs at nucleotide 1061 position in sample 2, however sample 1 did not have this mutation and the subgroup was not identified. DNA sequencing provides a precise and high accuracy in identification of A subgroups.